Forward interest rates and inflation expectations: The role of regime shift premia and monetary policy - Hans Dillén; Elisabeth Hopkins (Sveriges Riksbank, 1998)
In this paper we argue that there are two major explanations to why Swedish forward interest rates have been high and volatile: (i) Investors' fears that the economy will switch to a high inflation regime give rise to a regime shift premium. (ii) Expectations of monetary policy actions amplify the effect on forward interest rates originating from fluctuations in inflation expectations. In an empirical investigation the quantitative importance of adjusting forward interest rates for regime shift premia is demonstrated. In a second step it is shown that an one percentage point increase of the one year forward interest rate (adjusted for the regime shift premium) only corresponds to an increase of investors' inflation expectations (obtained from surveys) by approximately 0.2 percentage points, suggesting that the rest of the forward interest rate movement reflects expectations of future increases of the future real short term interest rate, i.e. a tightening of monetary policy. Finally, there is evidence that investors' inflation expectations from 4 to 2 percent mainly is due to a decrease of the regime shift premium
Keywords: 330